PENGARUH DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP KOMITMEN ORGANISASI PEGAWAI UNIVERSITAS MALIKUSSALEH DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Surito, Surito; Arifin, A. Hadi; Aiyub, Aiyub (Universitas Malikussaleh, 2019)
This study aims to examine the effect of work discipline, and the work environment on organizational commitment of Malikussaleh University with job satisfaction as intervening variable. This research is Quantitative research. The instrument of data collection is using questioner. Determination of respondents using Census techniques. Census is a sample determination technique that takes the entire population into samples. The population in this study was 158 employees at the University of Malikussaleh. The sample in this study that can be used amounted to 153 people while others are not in return. Data analysis using SPSS with path analysis and test sobel. The results of data analysis obtained work discipline, and work environment organizational commitment has a positive and significant impact on job satisfaction Malikussaleh University employees. Work discipline, work environment, and organizational commitment have a positive and significant impact on job satisfaction of Malikussaleh University civil servants. job satisfaction does not mediate the influence of work discipline on employee organizational commitment at Malikussaleh University job satisfaction does not mediate the influence of work environment on organizational commitment of employees at Malikussaleh University,Â Keywords : Work Discipline and Work Environment, Organizational commitment to Job Satisfaction